The Effect of Knowledge Management Operations on The Quality of Educational Services (An applied Study on College of Economic and Science in Tishreen University) (Journal of Hama University, 2020)
The researcher in this study is examining the impact of knowledge management operations on the quality of educational services in the College of Economis and Science in Tishreen University. The study sample included (196) members of the educational staff. The questionnaire was the main tool for collecting data. Some interviews were conducted to inquire about some issues. The data was analyzed using the statistical program (SPSS 20).The purpose of this study was to examine the impact of knowledge management operations on improving the quality of educational services, and highlighted the great significance of knowledge and the need to apply them in the colleges in order to improve the quality of the provided educational services. The concentration was on the (Identification, generation of knowledge – Conquest, storage knowledge, knowledge Diffusion and application) as the most knowledge management operations in the universities.One of the main results of the study was that there is a  positive relationship between relying on knowledge management operations and improving the quality of  the provided educational services. Thus, the more relying on implementation of knowledge management operations, the more it will improve the quality of the provided educational services. This was really clear in this field study since the impact of knowledge management operations  was on improving the quality, when Diffusion and storage knowledge were implemented in the College of Science and the quality of educational services increased when all the operations had been implemented in the College of Economics. knowledge Diffusion, Knowledge application, quality improvement, educational services).